Development of Skeletal Ossification in Climbing Perch (Anabas testudineus) from Juvenile to Adulthood - Pangestiningsih, Tri Wahyu; Wendo, Woro Danur; Kusindarta, Dwi Liliek (Jurnal Medik Veteriner, 2024)
The climbing perch (Anabas testudineus) is a freshwater fish that can withstand highly unfavorable environments and stay out of the water for extended periods. Its anatomical characteristics showed terrestrial adaptation and terrestrial locomotion properties enable the use of climbing perch as an animal model. Moreover, its bone and cartilage profiles at different stages are crucial to improving the anatomical information for the osteogenesis model candidate. The current study aimed to illustrate the skeletal profiles of juvenile and adult climbing perch with the whole staining method. The samples included two adults and two juvenile climbing perch from Daerah Istimewa Yogyakarta, Indonesia. The fish were euthanized using β-hydroxyethyl phenyl ether in a lethal dose. The skeleton was examined using the Alcian blue–Alizarin red whole staining, which revealed the bones and cartilage under the stereomicroscope. The result showed that the bone is the main skeleton. Cartilage was detected in the area surrounding the orbit in the adult climbing perch and in the pterotic, pterosphenoid, prootic, and distal end of the hypural, parhypural, and basal pectoral girdle in the juvenile climbing perch. Endochondral osteogenesis was found in juvenile to adult climbing perch.